The effect of cognitive behavioural group therapy on the workplace and decisional procrastination of midwives: A randomized controlled trial - Monireh Moharram-nejadifard; Omid Saed; SeyedeSolmaz Taheri; Elahe Ahmadnia (Wolters Kluwer Medknow Publications, 2020)
Background: Procrastination in the general population is a prevalent phenomenon. Procrastination in midwives, who are responsible for health care services, can have serious consequences and reduce health care productivity. Cognitive Behavioral Group Therapy (CBGT) is believed to reduce procrastination, but few studies have investigated its effectiveness. The aim of the present study was to determine the effect of CBGT on the workplace and decisional procrastination of midwives. Materials and Methods: This randomized, controlled trial was conducted on 47 participants who were eligible to participate in the study. The participants were randomly assigned to the CBGT (n = 24) and control (n = 23) groups. The intervention group received 7 sessions of CBGT and the control group received no intervention. Decisional and workplace procrastination were assessed at the pre-treatment, post-treatment, and 2-month follow-up phases. Repeated measures Analysis of Variance (ANOVA) and Analysis of Covariance (ANCOVA) were used for data analysis. Results: At the posttest and follow-up phases, workplace procrastination (Post-test: F1,40= 11.78, p = 0.001; Follow-up: F1,40= 11.12, p = 0.002), soldiering (Post-test: F1,40= 13.77, p = 0.001; Follow-up: F1,40= 4.15, p = 0.049), cyberslacking (Post-test: F1,40= 4.20, p = 0.047; Follow-up: F1,40= 13.34, p = 0.001), and decisional procrastination (Post-test: F1,40= 6.66, p = 0.014; Follow-up: F1,40= 6.12, p = 0.018) significantly decreased in the CBGT group compared to the control group. CBGT explained 23% of the changes in the total workplace procrastination score and 22% of the changes in the component of soldiering (p < 0.05). Conclusions: CBGT significantly reduced workplace and decisional procrastination in midwives.